Hoax: Teks dan Konteks dalam Al-Quran - Danu Aris Setiyanto (Indonesian Center for Religion and Society Studies (InTReSt), 2019)
The development of technology has been shifted human’s way from the manual era to the digital era. Humans have been able to communicate without border and time. However, information in the modern era is not always true and many of them are false or hoaxes. Al Qur’an as a guide for humans has actually explained the hoax. Some words in the Al Qur'an illustrated the context of hoaxes such as ifk, kaẑaba, fitnah, khud'a, qaul al-zūr, buhtan, iftara, tahrif, and garur. In this paper, it will discuss the text of the hoax in the Al Qur’an in its text and textual verses when the verse is revealed. Furthermore, the context of the hoax in the Al Qur’an is explained in the context of the current issues with a semantic approach. This paper concludes that the meaning of the hoax in the Al Qur'an is in accordance with the recent context but only the media and problems are more complex. Furthermore, the Qur'an has provided solution to the issues of hoax such as checking the correctness of the data before sharing (Q. S Al-Hujurat: 6, Q. S Isra: 36), increasing the culture of literacy (Q. S Al-Qalam: 1 -2), awareness of prejudice (Q. S Al-Hujurat: 12), and so on.